Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Cerita Sistem Persamaan Linear Dua Variabel - ., Ignasius Nong Mere (CV. ITTC INDONESIA, 2022)
This research aims to determine the types of student errors, as well as the factors that cause errors in solving SPLDV story problems. This research was conducted in class VIII F of SMP Negeri 1 Maumere which consisted of 27 students. Student error data obtained from the results of written tests. Student answers that are incorrectly identified into the type of error. After that, 3 students were selected as respondents to be interviewed. This research uses a qualitative approach and the type of research is descriptive. Data analysis was performed by data reduction, data presentation and conclusion. The results of the study showed that no students were able to answer all of the questions correctly. Based on the results of data analysis, it was concluded that the types of errors made by students were (1) conceptual errors of 44.75%; (2) principal errors of 34.04%; and (3) operating errors of 24.62%. Based on the results of the interviews, the factors that caused the mistakes made by students were because they did not understand the questions so they were unable to translate the question sentences into mathematical sentences, they were weak about the concept of variables, the elimination and substitution methods, they were weak in determining the results of calculations, and they lacked practice working on equation system questions linear two variables in the form of varied stories.